2005
DOI: 10.1074/jbc.m411556200
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Mechanical Unzipping of Amyloid β-Fibrils

Abstract: Amyloid fibrils are self-associating filamentous structures, the deposition of which is considered to be one of the most important factors in the pathogenesis of Alzheimer's disease and various other disorders. Here we used single molecule manipulation methods to explore the mechanics and structural dynamics of amyloid fibrils. In mechanically manipulated amyloid fibrils, formed from either amyloid ␤ (A␤) peptides 1-40 or 25-35, ␤-sheets behave as elastic structures that can be "unzipped" from the fibril with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
111
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(129 citation statements)
references
References 48 publications
13
111
5
Order By: Relevance
“…This method avoids indentation into the matrix, thus reduces the possibility of picking up multiple molecules in a single pull. Fitting the force curve with WLC model gave a persistence length of 0.35 ± 0.05 nm, which agrees pretty well with previous results on amyloid fibrils (Kellermayer, et al, 2005;. In addition, FT-IR spectroscopy and dye (Congo red and thioflavin T) staining confirmed the presence of -sheet and amyloid structures in the sample.…”
Section: Applicationssupporting
confidence: 77%
See 3 more Smart Citations
“…This method avoids indentation into the matrix, thus reduces the possibility of picking up multiple molecules in a single pull. Fitting the force curve with WLC model gave a persistence length of 0.35 ± 0.05 nm, which agrees pretty well with previous results on amyloid fibrils (Kellermayer, et al, 2005;. In addition, FT-IR spectroscopy and dye (Congo red and thioflavin T) staining confirmed the presence of -sheet and amyloid structures in the sample.…”
Section: Applicationssupporting
confidence: 77%
“…All of the force curves exhibited non-linear elastic mechanical response followed by one or several rupture events. The absence of force plateau, which is a characteristic pattern of the unzipping of -sheets from the fibril, implies that the high packing density in mature glucagon amyloid fibrils allows a stable confinement of the peptide molecules in the twisted fibrillar structure, in contrast to A amyloid fibrils (Karsai et al, 2006;Kellermayer, et al, 2005). The stable structure is further confirmed by repeatedly stretching a single fibril for 1000 times.…”
Section: Applicationsmentioning
confidence: 58%
See 2 more Smart Citations
“…More recently, Lim and coworkers showed that the elastic properties of blood clots are mainly determined by the coiled-coil helices of fibrinogen 142 . In another example, Kellermayer and coworkers described the structure and self assembly mechanism of amyloid β-fibrils 143 and myosin thick filaments 144 .…”
Section: Applications Of Afmmentioning
confidence: 99%